If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(b + -5) = 5z + -36 Reorder the terms: 4(-5 + b) = 5z + -36 (-5 * 4 + b * 4) = 5z + -36 (-20 + 4b) = 5z + -36 Reorder the terms: -20 + 4b = -36 + 5z Solving -20 + 4b = -36 + 5z Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 4b = -36 + 20 + 5z Combine like terms: -20 + 20 = 0 0 + 4b = -36 + 20 + 5z 4b = -36 + 20 + 5z Combine like terms: -36 + 20 = -16 4b = -16 + 5z Divide each side by '4'. b = -4 + 1.25z Simplifying b = -4 + 1.25z
| (4g+20)=(5g-2) | | 5(2x-6)-2(x+1)-20x= | | 3x-15=2x+21 | | 4(a-2)-2a=10+3(a-3) | | 8(x-3)=5(x+6)-15 | | 62=(x+3)+(x+5)+x | | 19z=380 | | 5=a+5-6 | | i-(-10)=6 | | 2x+18=3x-32 | | 12x+5=7y+10 | | w^2-2w+36= | | 62=(x+3)+(x+5) | | 2x+4(5-3x)=(9x-5) | | -3.5-.75b=-3.9 | | F(x)=10x^2+5x-7 | | 4x+2(x-25)=-20 | | 12*5=y | | (x/8)+8=9 | | 11-z=-3 | | 21x-63=3x+24 | | 13-3x=(x/4) | | Y-18=-7 | | 2x+5(x-14)=-7 | | 250-4x=85-6x | | 6(5x-9)=186 | | 5X+19X= | | -4(1-5x)=36 | | .714(t+7)=.3t+23 | | 2x+5(4x+4)=262 | | -4x+7-6(x-1)=-(3x-3)-6x+6 | | -11+7=-2(x+9) |